PENGARUH FINANCIAL TECHNOLOGY TERHADAP INKLUSI KEUANGAN UMKM PENGGUNA QRIS - Atarwaman, Rita; Gainau, Paskanova Christi; Muriany, Wildo Natalio Christo (Jurnal Akuntansi Kontemporer, 2023)
Research Purposes: This study aims to examine the effect of financial technology on financial inclusion in the coffee shop business, where financial technology is represented by cashless payment, market aggregator, risk and investment management.Research Methods: This study used a quantitative approach with survey method to coffee shop entrepreneurs who using QRIS in Ambon City.Research Results and Findings: The results show that partially cashless payment and market aggregator have a significant effect on financial inclusion, but risk and investment management has no effect on financial inclusion. The implication is for the government and financial institutions to socialize and educate MSME owners regarding the types of fintech risk and investment management so that MSME owners know and allocate funds for investment, because the development of MSMEs is able to boost the Indonesian economy.